Management of symptomatic uterine fibroids after ulipristal acetate suspension and identification of high risk patients for surgery at 6-months of follow-up. (2nd September 2021) - Nicolás, Inmaculada; Martínez-Zamora, María Ángeles; Gracia, Meritxell; Carrion, Ana; Feixas, Georgina; Bernal, Laura; Quintas, Lara; Rius, Mariona; Castelo-Branco, Camil; Carmona, Francisco
Abstract: Objective: The use of ulipristal acetate (UPA) was indicated for the treatment of uterine fibroids. Following UPA suspension in March 2020, some patients presented worsening and required surgery. We aimed to identify patients at high-risk for undergoing surgery after UPA suspension. Methods: We evaluated 85 women receiving intermittent UPA treatment until March 2020. Following UPA suspension, patients received other medical treatments or surgery. The clinico-pathological features were recoded and a quality of life health survey was completed by patients at the time of UPA suspension and at 6-months thereafter. Results: After the suspension of UPA, 17 of the 85 patients receiving intermittent UPA (20%) required surgery, and 68 (80%) required other medical treatments. Patients who underwent surgery were younger and had greater fibroid volume. Conclusions: In our series, 20% of clinically stable patients receiving intermittent UPA required surgery following UPA suspension. These women should be considered for future medical strategies.